Analysis and Suppression of Torque Ripple for Doubly Salient Electro-Magnetic Motor - Le Zhang; Bo Zhou; Fang-Shun Cheng (2009 IEEE Industry Applications Society Annual Meeting, 2009)
The doubly salient electro-magnetic motor (DSEM) is subject to significant torque ripple when working with traditional standard angle control method. To weaken the effects of the torque ripple for further applications of DSEM such as wind power generation and aerospace, in-depth analysis of the ripple generation mechanism and two novel strategies of inner torque loop and torque distribution control are presented in this paper. In conclusion, simulation and comparative analysis of the two strategies are conducted with a 2kW 12/8 DSEM prototype. The simulation results demonstrate that, compared with traditional control methods, the two novel torque control strategies can effectively suppress DSEM torque ripple.